Study of isomeric states in 198, 200, 202, 206Pb and 206Hg populated in fragmentation reactions. (12th February 2018) - Lalović, N; Rudolph, D; Podolyák, Zs; Sarmiento, L G; Simpson, E C; Alexander, T; Cortés, M L; Gerl, J; Golubev, P; Ameil, F; Arici, T; Bauer, Ch; et al.
Abstract: Isomeric states in isotopes in the vicinity of doubly-magic 208 Pb were populated following reactions of a relativistic 208 Pb primary beam impinging on a 9 Be fragmentation target. Secondary beams of 198, 200, 202, 206 Pb and 206 Hg were isotopically separated and implanted in a passive stopper positioned in the focal plane of the GSI Fragment Separator. Delayed γ rays were detected with the Advanced Gamma Tracking Array (AGATA). Decay schemes were re-evaluated and interpreted with shell-model calculations. The momentum-dependent population of isomeric states in the two-nucleon hole nuclei 206 Pb/ 206 Hg was found to differ from the population of multi neutron-hole isomeric states in 198, 200, 202 Pb.